MODELLING OF DATA WAREHOUSE WITH MAKING THE TREND TO MAKE DECISION IN COMPANY XYZ - Dwi Sartika simatupang; Anggun Fergina; Bahadir Ozsut (INTERNATIONAL JOURNAL ENGINEERING AND APPLIED TECHNOLOGY (IJEAT), 2022)
The goals of the thesis were to modellig a data warehouse which was loaded from the operational database PT. XYZ, to analyze data warehouse with Tableau Software to know the trends of activity Trouble ticket, and to create reports and dashboards to facilitate PT. XYZ in viewing the trends. Data were compiled by observation to PT. XYZ from reporting team. Data were analyzed using software tableau. The results obtained were the trend of activity trouble ticket more than two hundred thousand data in sixteen weeks or four month in 2017. It can be concluded that developed data warehouse can be used to analyze in gaining information about the trends of activity trouble ticket and help to make a decision.